CFD simulation of mixing in tall gas-liquid stirred vessel: role of local flow patterns - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Chemical Engineering Science, 2006)
In this work, we have used the computational fluid dynamics (CFD)-based models to investigate the gas-liquid flows generated by three down-pumping pitched blade turbines. A two-fluid model along with the standard k-epsilon turbulence model was used to simulate the dispersed gas-liquid flow in a stirred vessel. Appropriate drag corrections to account for bulk turbulence [Khopkar and Ranade, 2005. CFD simulation of gas-liquid flow in a stirred vessel: VC, S33 and L33 flow regimes. A.I.Ch.E. Journal, accepted for publication] were developed to correctly simulate different flow regimes. The computational snapshot approach was used to simulate impeller rotation and was implemented in the commercial CFD code, FLUENT4.5 (of Fluent. Inc., USA). The computational model has successfully captured the flow regimes as observed during experiments. The particle trajectory simulations were then carried out to examine the influence of the different flow regimes on the circulation time distribution. The model predictions were verified by comparing the predicted results with the experimental data of [Shewale and Pandit, 2006. Studies in multiple impeller agitated gas-liquid contactors. Chemical Engineering Science 61, 489-504]. The computational model and results discussed in this study would be useful for explaining the implications local flow patterns on the mixing process and extending the applications of CFD models for Simulating large multiphase stirred reactors. (c) 2005 Elsevier Ltd. All rights reserved.
7th International Conference on Fluid Mixing, London, ENGLAND, APR 10-12, 2006
Keywords: CFD; Flow regimes; mixing; pitched blade turbine; stirred vessel

Computational fluid dynamics simulation of the solid suspension in a stirred slurry reactor - Khopkar, A. R.; Kasat, Gopal R.; Pandit, A. B.; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
A comprehensive computational fluid dynamics CFD model was developed in the present study to gain insight into the solid suspension in a stirred slurry reactor. The preliminary simulations highlighted the need for the correct modeling of the interphase drag force. A two-dimensional model problem was then developed using CFD to understand the influence of free stream turbulence on the particle drag coefficient. The proposed correlation was then incorporated in a two-fluid model (Euler-Euler) along with the standard k-epsilon turbulence model with mixture properties to simulate the turbulent solid-liquid flow in a stirred reactor. A multiple reference frame approach was used to simulate the impeller rotation in a fully baffled reactor. A computational model was mapped on to a commercial CFD solver FLUENT6.2 (of Fluent Inc., USA). The model predictions were compared with the published experimental data of Yamazaki et al. [Powder Technol. 1986, 48, 205] and Godfrey and Zhu [AIChE Symp. Ser. 1994, 299, 181]. The predicted results show reasonably good agreement with the experimental data. The computational model and results discussed in this work would be useful for extending the applications of CFD models for simulating large stirred slurry reactors.

CFD simulation of gas-liquid flows in a reactor stirred by dual rushton turbines - Kasat, Gopal R.; Pandit, Aniruddha B.; Ranade, V. V. (International Journal of Chemical Reactor Engineering, 2008)
In the present work, we have simulated gas-liquid flows in a tall stirred reactor equipped with dual Rushton turbines. A two fluid model along with the standard k-epsilon turbulence model and modified drag coefficient, (proposed by Khopkar & Ranade, 2006) accounting for the effect of bulk turbulence, was used to simulate the dispersed gas-liquid flow in a stirred reactor. The multiple reference frames (MRF) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc. USA). The model was used to simulate three distinct flow regimes in a gas-liquid stirred reactor: L33-VC (lower impeller-upper impeller), S33-VC and VC-VC. The model predictions were compared with the published experimental data of Bombac & Zun (2000). The predicted results show good agreement with the experimental data for all the three flow regimes. The computational model presented in this work would be useful for simulating different flow regimes in a gas-liquid stirred vessel.
Keywords: computational fluid dynamics; dual Rushton turbine; Flow regimes; gas hold-up distribution; stirred reactor

CFD simulation of liquid-phase mixing in solid-liquid stirred reactor - Kasat, Gopal R.; Khopkar, A. R.; Ranade, V. V.; Pandita, A. B. (Chemical Engineering Science, 2008)
A comprehensive CFD model was developed to gain an insight into solid suspension and its implications on the liquid-phase mixing process in a solid-liquid stirred reactor. The turbulent solid-liquid flow in a stirred reactor was simulated using a two-fluid model with the standard k-epsilon. turbulence model with mixture properties. The multiple reference frames (MRFs) approach was used to simulate impeller rotation in a fully baffled reactor. The computational model with necessary sub-models was mapped on to a commercial solver FLUENT 6.2 (of Fluent Inc., USA). The predicted solid concentration distribution was compared with the experimental data of Yamazaki et al. [ 1986. Concentration profiles of solids suspended in a stirred tank. Powder Technology 48, 205-216]. The computational model was then further extended to simulate and understand the implications of the suspension quality on liquid-phase mixing process. The computational model and the predicted results discussed here will be useful for understanding the liquid-phase mixing process in stirred slurry reactors in various stages of solid suspension. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: CFD; mixing; solid suspension; stirred reactor